2013
DOI: 10.1038/oncsis.2013.7
|View full text |Cite
|
Sign up to set email alerts
|

The EGFR family members sustain the neoplastic phenotype of ALK+ lung adenocarcinoma via EGR1

Abstract: In non-small cell lung cancer (NSCLC), receptor tyrosine kinases (RTKs) stand out among causal dominant oncogenes, and the ablation of RTK signaling has emerged as a novel tailored therapeutic strategy. Nonetheless, long-term RTK inhibition leads invariably to acquired resistance, tumor recurrence and metastatic dissemination. In ALK+ cell lines, inhibition of ALK signaling was associated with coactivation of several RTKs, whose pharmacological suppression reverted the partial resistance to ALK blockade. Remar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 49 publications
3
44
0
Order By: Relevance
“…In keeping with the mRNA data, the protein expression levels of PRL-1 decreased and were dependent on ALK kinase activity (Figure 3C). Interestingly, one of the genes identified in the screening with the RT 2 Profiler PCR array was ERBB3 that was strongly up-regulated after ALK inhibition both as mRNA (Figure 2B) and protein (Supplementary Figure 1A), consistent with our previous findings [43]. …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In keeping with the mRNA data, the protein expression levels of PRL-1 decreased and were dependent on ALK kinase activity (Figure 3C). Interestingly, one of the genes identified in the screening with the RT 2 Profiler PCR array was ERBB3 that was strongly up-regulated after ALK inhibition both as mRNA (Figure 2B) and protein (Supplementary Figure 1A), consistent with our previous findings [43]. …”
Section: Resultssupporting
confidence: 90%
“…In contrast, in H2228 cells treatment with TAE-684 increased cell migration and invasion, suggesting the activation of compensatory pathways to sustain or even increase this phenotype (Supplementary Figure 5A-5B). We and others previously demonstrated that the EGFR family members can induce resistance to ALK TKIs by activating by-pass compensatory signaling pathways in ALK-rearranged NSCLC [43, 46, 47] and are associated to EMT in different tumors types [48, 49]. Since we observed an up-regulation of both mRNA and protein levels of ERBB3 in TAE-684-inhibited H2228 cells (Figure 2B and Supplementary Figure 1A), we hypothesized an involvement of ERBB receptors in TAE-684 induced increased migration in H2228 cells.…”
Section: Resultsmentioning
confidence: 99%
“…S5E). To further confirm that PD-L1 expression was driven by ALK activity, and to exclude that PD-L1 down-regulation was mediated by crizotinib inhibition of MET, ROS1, or other off-targets, we knocked down EML4-ALK by a doxycycline inducible shRNA system (16). Again, PD-L1 expression was down-regulated upon EML4-ALK knock-down (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Next-generation ALK TKIs, such as ceritinib and alectinib, have been developed to overcome crizotinib resistance and can further extend survival in crizotinib-resistant patients (1012). Resistance to ALK TKIs is mediated by point mutations of the ALK kinase domain, by ALK gene amplification, or by activation of other compensatory pathways, so-called bypass tracks, such as EGFR, c-KIT, c-MET, and IGF-R1 (8,1316). Thus, additional therapies to be combined with ALK TKIs are needed to further prolong remission or clinical response in NSCLC patients with ALK rearrangements.…”
Section: Introductionmentioning
confidence: 99%
“…In ALCL, ALK oncogenic signals are mediated by a series of key molecules and pathways, including STAT3, PI3K, RAS/MAPK/ERK, SHP2, p130CAS, PLCg, and Src (2,5). In NSCLC, conversely, downstream pathways are less extensively characterized (6).…”
Section: Introductionmentioning
confidence: 99%